Pengaruh Implementasi E-Filing, Pengetahuan Perpajakan, Sanksi Pajak Dan Religiusitas Wajib Pajak Terhadap Kepatuhan Wajib Pajak Pada Masa Pandemi Covid-19 - Jumriyah, Jumriyah; Faisol, Imam Agus (Unversitas Islam Madura, 2023)
This study aims to analyze the effect of e-filing implementation, tax knowledge, tax sanctions, and taxpayer religiosity on individual taxpayer compliance in Bangkalan Regency during the Covid-19 pandemic. This research is a type of quantitative research. The population in this study is an individual taxpayer who is in Bangkalan district registered at KPP Pratama Bangkalan. The number of individual taxpayers registered with KPP Pratama Bangkalan in 2021 is 183,995. The sampling technique used a random sampling technique with the calculation of the Hair formula in order to obtain 165 individual taxpayers who became respondents. Data were collected by distributing questionnaires directly to respondents. The data analysis technique used in this research is PLS SEM using Smart-PLS 3.0 software. The results of this study indicate that, the implementation of e-filing, knowledge of taxation, tax sanctions, and religiosity partially affect the compliance of individual taxpayers in Bangkalan Regency. the implementation of e-filing, knowledge of taxation, tax sanctions, and taxpayer religiosity simultaneously affect the compliance of individual taxpayers in Bangkalan Regency.